Agama Dan Kesehatan Mental - Matnur Ritonga (STAI Siliwangi Bandung, 2017)
Humans are essentially born in a state of fitrah (holy, clean, straight, and mentally healthy). A man with two main tasks, namely: as' Abdun (servant of God), also as Caliph (Ruler of theearth). So Allah SWT install on human things ranging from hardware (al-hawas al-khams and other members of jasadiyah) and software (al-ruh, al-'aql, al-nafs, al-qalb) as a means to carry out the two mandates. Selected human beings are inspired even karomah. Those who are able to use all the grace will be mentally healthy, through the process: learning (iqro: qur'aniyah verses & verses kauniyah), will produce: faith, islam, and ihsan. Are those who do not want to explore the potential within him will be mentally ill if the category: nifaq even kufr. Those who are sick mentally will never know and realize that they are sick. It is obtained from the Mafhun mukhalafah in a hadith it is said: